ENHANCEMENT OF ACCESS AND UTILISATION OF PRIMARY HEALTH CARE SYSTEM: A MICRO LEVEL ANALYSIS IN TAMIL NADU (CAHIERS MAGELLANES-NS, 2024)
The health indicators at the macro level show that there has been an overall improvement in the people's health status in rural areas. The mission of the National Rural Health Mission is to ensure that the most vulnerable people in rural regions have access to healthcare that is both inexpensive and of high quality. The establishment of a health delivery system that is completely functioning, owned by the community, and decentralized has been given priority in order to provide the most advantages possible to those who are in need. At the same time, there is a pressing need to conduct an analysis of the manner in which the public healthcare system serves rural residents. In this regard, a study on a micro level was carried out, and it covered a total of 281 households that had received care from one of three Upgraded Primary Health Centres located in the Namakkal District of Tamil Nadu. Interviewing individuals directly allowed for the collection of the necessary information and data.The data that were acquired were examined by taking their percentages, finding their Mean, and doing Regression. According to the findings, the physical accessibility of the Upgraded Primary Health Centre to the households that were chosen to participate in the study was significantly improved. At the same time, it was discovered that inadequate use of healthcare services was taking place. It was observed that financial restrictions and also the mentality of the people, who tend to go for private hospitals, were the reasons behind this fact. Both of these factors contributed to the situation. On the basis of the findings, it has been indicated that there is a requirement for the Upgraded Primary Health Centres to improve the quality of the services that they offer.